2016
DOI: 10.1002/anie.201509472
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Organocatalytic Diels–Alder Trapping of Photochemically Generated Hydroxy‐o‐Quinodimethanes

Abstract: The photoenolization/Diels–Alder strategy offers straightforward access to synthetically valuable benzannulated carbocyclic products. This historical light‐triggered process has never before succumbed to efforts to develop an enantioselective catalytic approach. Herein, we demonstrate how asymmetric organocatalysis provides simple yet effective catalytic tools to intercept photochemically generated hydroxy‐o‐quinodimethanes with high stereoselectivity. We used a chiral organic catalyst, derived from natural ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
50
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(55 citation statements)
references
References 29 publications
1
50
0
4
Order By: Relevance
“…Synthetisiert wurden diese Verbindungen ausgehend von den Diolen 1-4 nach der in Schema 1angegebenen Syntheseroute.K eton 5,d as die Endgruppe festlegt, wurde nach einer abgewandelten bekannten Vorschrift hergestellt [23] und anschließend in die Acetylenbausteine 6-8 umgewandelt (siehe die Hintergrundinformationen fürDetails). Synthetisiert wurden diese Verbindungen ausgehend von den Diolen 1-4 nach der in Schema 1angegebenen Syntheseroute.K eton 5,d as die Endgruppe festlegt, wurde nach einer abgewandelten bekannten Vorschrift hergestellt [23] und anschließend in die Acetylenbausteine 6-8 umgewandelt (siehe die Hintergrundinformationen fürDetails).…”
unclassified
“…Synthetisiert wurden diese Verbindungen ausgehend von den Diolen 1-4 nach der in Schema 1angegebenen Syntheseroute.K eton 5,d as die Endgruppe festlegt, wurde nach einer abgewandelten bekannten Vorschrift hergestellt [23] und anschließend in die Acetylenbausteine 6-8 umgewandelt (siehe die Hintergrundinformationen fürDetails). Synthetisiert wurden diese Verbindungen ausgehend von den Diolen 1-4 nach der in Schema 1angegebenen Syntheseroute.K eton 5,d as die Endgruppe festlegt, wurde nach einer abgewandelten bekannten Vorschrift hergestellt [23] und anschließend in die Acetylenbausteine 6-8 umgewandelt (siehe die Hintergrundinformationen fürDetails).…”
unclassified
“…6 But methods that use substoichiometric chiral catalysts remained unprecedented until recently, when our research group reported an organocatalytic strategy for successfully trapping A in a stereoselective fashion. 7 Our approach relied on the use of a chiral organic catalyst which could effectively activate the dienophilic maleimide D (Figure 1c). Building upon this precedent, we wondered whether organocatalysis 8 could offer other effective tools to stereoselectively trap photogenerated hydroxy-o-quinodimethanes A with different dienophiles.…”
mentioning
confidence: 99%
“…11 We also tested the catalytic profile of 5c, since it provided the best results in our previous study on the stereocontrolled trapping of photoenol A with maleimides of type D (Figure 1c). 7 The experiments were performed over 14 hours, in toluene, at ambient temperature, and under irradiation by a single black-light-emitting diode (black LED, λmax = 365 nm). Benzaldimines bearing commonly used N-protecting groups, including N-Boc, N-tosyl, and N-PMP imines (Boc = tert-butyloxycarbonyl; tosyl = toluenesulfonyl; PMP = p-methoxyphenyl), did not lead to the formation of any product, and were recovered untouched.…”
mentioning
confidence: 99%
See 2 more Smart Citations